Eschar removal by bromelain based enzymatic debridement (Nexobrid) in burns: European consensus guidelines update - Hirche, Christoph; Kreken Almeland, Stian; Dheansa, Baljit; Fuchs, Paul; Governa, Maurizio; Hoeksema, Henk; Korzeniowski, Tomasz; Lumenta, David B.; Marinescu, Silviu; Martinez-Mendez, José Ramón; Plock, Jan A.; Sander, Frank; et al. (Burns, 2020)
Introduction - Bromelain-based Enzymatic Debridement has been introduced as an additional concept to the burn surgeon's armamentarium and is best indicated for mid-to deep dermal burns with mixed patterns. Increasing evidence has been published focusing on special regions and settings as well as on limitations of Enzymatic Debridement to improve patient care. To better guide Enzymatic Debridement in view of the increasing experience, there is a need to update the formerly published consensus guidelines with user-orientated recommendations, which were last produced in 2017. - Methods - A multi-professional expert panel of plastic surgeons and burn care specialists from twelve European centers was convened, to assist in developing current recommendations for best practices with use of Enzymatic Debridement. Consensus statements were based on peer-reviewed publications and clinical relevance, and topics for re-evaluation and refinement were derived from the formerly published European guidelines. For consensus agreement, the methodology employed was an agreement algorithm based on a modification of the Willy and Stellar method. For this study on Enzymatic Debridement, consensus was considered when there was at least 80 % agreement to each statement. - Results - The updated consensus guidelines from 2019 refer to the clinical experience and practice patterns of 1232 summarized patient cases treated by the panelists with ED in Europe (2017: 500 cases), reflecting the impact of the published recommendations. Forty-three statements were formulated, addressing the following topics: indications, pain management and anesthesia, large surface treatment, timing of application for various indications, preparation and application, post-interventional wound management, skin grafting, outcome, scar and revision management, cost-effectiveness, patient´s perspective, logistic aspects and training strategies. The degree of consensus was remarkably high, with consensus in 42 out of 43 statements (97.7%). A classification with regard to timing of application for Enzymatic Debridement was introduced, discriminating immediate/very early (≤12 h), early (12−72 h) or delayed (>72 h) treatment. All further recommendations are addressed in the publication. - Conclusions - The updated guidelines in this publication represent further refinement of the recommended indication, application and post-interventional management for the use of ED. The published statements contain detailed, user-orientated recommendations aiming to align current and future users and prevent pitfalls, e.g. for the successful implementation of ED in further countries like the USA. The significance of this work is reflected by the magnitude of patient experience behind it, larger than the total number of patients treated in all published ED clinical trials.